Prediksi Produksi cabai rawit (Capsicum Frutescens L.) di Provinsi Lampung menggunakan POM-QM. - Ulfah Izdihar; Nurbaiti; Radya Yogautami; Ayu Rahayu Saraswati (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
Lampung Province has great potential in developing horticultural commodities, particularly chili (Capsicum frutescens L.), which is a strategic commodity for farmers’ livelihoods and national food price stability. However, chili production in Lampung often fluctuates due to seasonal factors, climate change, pest attacks, limited farmer capital, and market conditions. This study aims to forecast chili production in Lampung Province using POM-QM software with the Linear Regression method based on historical production data from 2020–2023 obtained from BPS. The data were processed using POM-QM version 5 to predict production for the 2024–2027 period. The results indicate that the most appropriate forecasting method for predicting cayenne pepper production in Lampung Province was Linier Regression, as it produced the lowest Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE) values, namely 1,192.25 and 9.76%, respectively. The linear regression model obtained was y = 1080.9x – 2E+06, with a coefficient of determination R2 of 0.7503, indicating that the model adequately explained the variation in production data. Based on this model, the forecasted cayenne pepper production in 2027 is 12,488